Aplikasi Perbaikan Citra Digital Berbasis Android Dengan Metode Histogram Equalization - Matondang, Zekson Aizona; Pasaribu, Maranata (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2024)
Digital images (photos) have become an integral part of everyday life. This is supported by the increasingly sophisticated technology today where communication devices such as mobile phones can also use their role to replace analog cameras to take pictures or even record videos. Capturing happy moments or just wanting to record an event has become very easy to do, but sometimes the resulting photos are less than satisfactory due to the specifications of the mobile phone itself or other factors such as poor lighting (dark). Improvement efforts are also very necessary, but because the application to do this is only available on computers and not too many on mobile phones, this becomes difficult to do. One method in image improvement is the Histogram Equalization method. This method can be used to improve image quality related to lighting, namely by maintaining color constancy. The use of this histogram equalization method is considered easy because of its efficiency and relatively better performance on almost all types of images. The operation of HE (Histogram Equalization) is carried out by remapping the gray image level based on the probability distribution of the input gray level. It horizontally and dynamically stretches the various histograms of the image and produces an overall increase in contrast.